Citizens opinions, experiences and perceptions about waiting lists for elective cataract surgery and hip and knee replacement. - Sampietro-Colom, L; Espallargues, M; Reina, MD; Marsó, E; Valderas, J; Estrada, MD (2004)
OBJECTIVES: The aim of this study is to describe the views, perceptions and personal experience around elective cataract and hip and knee replacement waiting lists in Catalonia in order to improve their management. DESIGN: Qualitative methodology: four focus groups for each procedure. PLACE: Conducted between February-March 2000 at the Catalan Health Services headquarters. PARTICIPANTS: Each focus group included consultants (ophtalmologists, orthopedic surgeons, rheumatologists, rehabilitators, GPs), other related health professionals (nurses, social workers, physiotherapists, opticians/optometrist, GPs), patients and relatives and general population. Participants were selected through researchers and the clinical scientific committees. All of them followed a pre-established inclusion criteria. MAIN MEASURES: The analysis of the information was performed using the content analysis technique (contents of sessions were transcripted and information classified according to themes). RESULTS: Ten themes were identified. Waiting lists were argued to be a consequence of lack of resources, bad management and conflict of interest among consultants. Overall, the health care authority responsibility for the solution was acknowledged, although some participants claim more citizen participation. Among proposed solutions, prevention and education, more resources and improved management were found. Furthermore, a better physician-patient communication was considered essential. All the groups disagreed with the implicit current prioritisation system, however none wanted to assume the responsibility. CONCLUSIONS: Citizen's perceptions and personal experiences point to a multifactorial approach to waiting lists management, which would ameliorate the problem and lead to a better social acceptance.